2011
DOI: 10.21435/sflin.16
|View full text |Cite
|
Sign up to set email alerts
|

Representations of Finnishness in Sweden

Abstract: The Finnish Literature Society (SKS) was founded in 1831 and has, from the very beginning, engaged in publishing operations. It nowadays publishes literature in the fields of ethnology and folkloristics, linguistics, literary research and cultural history. The first volume of the Studia Fennica series appeared in 1933. Since 1992, the series has been divided into three thematic subseries: Ethnologica, Folkloristica and Linguistica. Two additional subseries were formed in 2002, Historica and Litteraria. The sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
11
0
2
Order By: Relevance
“…In those rare studies where participant observation of focus groups has been used, it has been noticed that humor functions as a mechanism through which group identities become established, "materialized" if you like (see Terrion and Ashforth, 2002;Kuipers, 2010). For instance, in group discussion studies conducted earlier in Sweden it was noticed how, compared to other discourses, narrations of Finnishness were invariably played down with laughter (Weckström, 2011). Similarly, in focus group discussions humor has been used as an alternate research method through which intimately political conversations about everyday practices can be accessed (Browne, 2016).…”
Section: Methodologies Of Hearing Stories and Laughing In Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…In those rare studies where participant observation of focus groups has been used, it has been noticed that humor functions as a mechanism through which group identities become established, "materialized" if you like (see Terrion and Ashforth, 2002;Kuipers, 2010). For instance, in group discussion studies conducted earlier in Sweden it was noticed how, compared to other discourses, narrations of Finnishness were invariably played down with laughter (Weckström, 2011). Similarly, in focus group discussions humor has been used as an alternate research method through which intimately political conversations about everyday practices can be accessed (Browne, 2016).…”
Section: Methodologies Of Hearing Stories and Laughing In Groupsmentioning
confidence: 99%
“…A number of studies on humor have explicitly pointed out how group identities are embedded as well as established 6 6 through storied humor (e.g. Rothwell et al, 2011;Weckström, 2011). In fact, in Finnish words 'joke' and 'story' have a common etymological origin (Knuuttila, 1992).…”
Section: Spatial Identities Narrations and Humormentioning
confidence: 99%
“…Många ungdomar med invandrarbakgrund vill gärna identifiera sig med majoritetsungdomar för att höja sin status och därför väljer de att tala majoritetsspråket (Maehlum, 2007). Även föräldrar med minoritetsbakgrund kan börja tala majoritetsspråket med sina barn av samma orsak (Weckström, 2008). Barn och ungdomar är mycket känsliga för omgivningens åsikter om vilket språk de skall använda i olika situationer (Baker, 2007, s. 7-9;Caldas 2006, s. 114-115).…”
Section: Teoretiska Utgångspunkterunclassified
“…Thus, it is hardly surprising that recent studies have found that many second-generation Finns might have a rather mixed and hybrid The Finnish and Swedish Migration Dynamics 109 identity. For example, among the second and third generation born in Sweden, the identification as a 'Sweden-Finn' is not necessarily very strong, and to move to Finland is not in the same way regarded as a 'return' as among the first generation (Ågren 2006;Weckström 2008;Björklund 2010). In this respect, there are clear similarities with results from other studies of second-generation engagement with the presumed 'homeland' (e.g.…”
Section: Number Of Migrantsmentioning
confidence: 99%
“…Later generations of Finnish ancestry often have a complex and hybrid identity and the knowledge of the Finnish language might be limited (cf. Weckström 2008). In short, there has been a process of integration, or even assimilation, taking place in Sweden, and the transnational social space created by the postwar labor migration seems to slowly 'melt into the core' of mainstream Swedish society.…”
Section: The Development Of the Transnational Social Space Over Timementioning
confidence: 99%